La télévision, les nouveaux rôles et espaces publics féminins dans les sociétés arabes contemporaines - Hasna Hussein (Les Cahiers d’EMAM)
Over the past 14 years, there has been an exponential increase of satellite TV channels in the Arab World. The influential presence of anchorwomen in Arab Satellite Channels is an irreversible phenomenon. It is increasingly changing the image of Arab women and reshaping their social perception and position within the society. This paper focuses on these transformations through the presence of anchorwomen in social and political TV talk-shows and reporting. In this context, it will be argued that anchorwomen’s new visibility in Arab satellite channels affects women’s professional situation, shapes gender roles, extends women’s participation in the Arab public sphere and enhances their sociopolitical role within the society at large.